Barriers to Collaborative Research in Education: A Study of Higher Education Lecturers - Habibat Bolanle ABDULKAREEM; Muhydeen Olaitan ABIOLA (Universitas Pendidikan Ganesha, 2026)
Although collaborative research is globally recognized as a driver of academic quality, relevance, and scholarly impact, the level of research collaboration in higher education institutions in Kwara State, Nigeria, remains relatively low, with many academics continuing to conduct research individually. This study investigates the perceived importance of collaborative research and the major barriers hindering its practice among lecturers in universities, polytechnics, and colleges of education. A descriptive survey design was employed to explore perceptions, patterns, and constraints associated with collaborative research practices. The study population comprised academic staff from universities, polytechnics, and colleges of education in Kwara State. A multistage sampling procedure was utilized to ensure representation across institutions and academic ranks, resulting in a sample of 150 lecturers. Data were collected using a structured instrument titled Barriers to Collaborative Research among Higher Education Lecturers Questionnaire (BCRHELQ), which consisted of four sections covering demographic information, perceptions of the importance of collaborative research, identified barriers, and proposed improvement strategies. Items were measured on a five-point Likert scale. Content validity was established through expert review, and reliability was confirmed using Cronbach’s alpha coefficient. Data collection was conducted both physically and online with the assistance of trained research assistants. The findings reveal a strong consensus regarding the benefits of collaborative research, including enhanced research quality, improved access to funding, mentorship opportunities, and greater policy relevance. However, significant barriers were identified, with inadequate research funding emerging as the most prominent constraint.